Inclusão escolar na escola professora Maria Amoras no município do Acará - PAULA, Cirlene Lisboa de (2021)
The present Course Conclusion Paper was built with focus on Inclusive Education that has been presented as a new educational paradigm, a recent fact in Brazilian education. It has gained strength with studies that have emerged and with proposals based on current legislation and educational practices. With this approach, the CBT aims to make a brief appreciation of the educational policies for Inclusive Education in Brazil, listing its historical evolution and conceptual framework. To this end, the qualitative approach was used and will be based on Brazilian legislation, specific policy guidelines of the Ministry of Education (MEC) and some documents used. The 1986 National Education Guidelines and Bases Act and the Salamanca Declaration made important advances in including education legislation. It is essential that there is even an education where students are respected and receive a teaching that respects their limitations, their differences and their particularities. Where the teacher seeks continuing education so that he can do his job better when he comes across students with special educational needs. Schools need to review their Curriculum and Pedagogical Policy Project, as these have little to contribute to the advancement of disabled students. These have a fundamental role in the teaching-learning process, they need to value a teaching that takes into account the differences of each subject. Longing, dreaming and overcoming were the key points for the construction of this TTC, there were many difficulties and anguish lived and felt, as well as the achievements and transformations achieved throughout the educational process. Describing it was challenging, but with great satisfaction and immense gratitude for the transformations achieved during this arduous academic journey. The references mentioned in the course of this narrative and which supported this work were: Bueno (1999), Freire (1996, 2005), Fumegalli (2012), Gadotti (1994), Mantoan (1997, 2002, 2003, 2006), Stainback (1999), among others.